Classification of Match Phases in Handball - Maurer, M. W.; Kautz, T.; Schlenzig, A.; Hiemann, A.; Zrenner, M.; Eskofier, B. M. (Sportinformatik XII. 12. Symposium der dvs-Sektion "Sportinformatik und Sporttechnologie" vom 5.-7. September 2018 in Garching. Abstracts., 2018)
Handball is a team sport with similar goals as soccer, basketball or hockey: One team aims at scoring a goal while the other team tries to prevent that. As in other team sports, tactics are a key ingredient for success. In contrast to soccer or basketball, there are only few publications dealing with handball tactic analysis. They are based on trajectories extracted from video data or video data is directly processed. We have recorded handball position data of ten matches using a local positioning system (LPS). Based on the data we extract match phases using machine learning to support coaches in the analysis of their teams` tactics.